8주간의 저항성운동 및 열량 감소식이가 비만 중년 흰쥐의 Traf2- NFkB-mTOR 및 SIRT1-FoxO1 신호인자의 발현에 미치는 영향 - 정수련; 안나영; 박주식; 김기진 (Exercise science (Seoul, Korea), 2018)
PURPOSE: The purpose of this study was to investigate the effect of 8-week calorie reduction and resistance exercise on the expression of Traf2-NFkB-mTOR and SIRT1-FoxO1 signal of cardiac muscle in obese middle aged rats. METHODS: 50 weeks old male Wistar rats were induced to obese by high fat diet treatment for 6 weeks after 1 week of environmental adaptation and then were randomly assigned to 4 groups (control group, CON; diet control with calorie reduction group, DC; resistance exercise group, RE; diet control and resistance exercise group, DRE). After that ladder climbing exercise or calorie reduction with general formula were treated for 8 weeks. RESULTS: Body weight and abdominal fat were significantly (p<.05) lower in the two groups as DC and DRE than the other groups as CON and RE. There was no significant difference in the weight of heart and skeletal muscle. Eight weeks of exercise or caloric reduction diet significantly (p<.05) reduced gene expression and activity of Traf2-NFkB-mTOR, which is a hypertrophic factor of cardiac muscle in obese middle-aged rats, and that autophagy factors of SIRT1-FoxO1 gene expression and activity were significantly (p<.05) increased. However, there was no synergistic effect with the combined treatment of the two stimuli. CONCLUSIONS: These results suggest that caloric reduction with weight loss or resistance training may be effective in preventing cardiac hypertrophy and heart failure in middle-aged obese rats. KCI Citation Count: 0